GAMBARAN KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI UPTD SMPN SATAP 2 GANTAR - Abdul Rosid; Dr. Dewi Cahyani, M.M.,M.Pd.; Dr. Moh. Ali, M.Pd.I. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine and analyze the influence of the principal's interpersonal communication on teacher performance at the UPTD SMPN Satu Atap 2 Gantar. A qualitative, descriptive approach was used. Data were obtained through in-depth interviews, observations, and documentation of the principal and teachers. The results indicate that the principal's interpersonal communication plays a crucial role in building harmonious working relationships, increasing motivation, and fostering a sense of responsibility for their duties. Principals who communicate openly, empathetically, and supportively have been shown to improve teacher performance in both lesson planning, lesson implementation, and assessment of learning outcomes. This study recommends that principals continue to develop their interpersonal communication skills within the context of participatory leadership.